2016
DOI: 10.1007/s00383-016-3918-x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers in pediatric appendicitis

Abstract: LRG, adjusted for dehydration, is a promising novel urinary biomarker for appendicitis in children. LRG in combination with PAS has a high diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…The actual feasibility and logistic of analyzing urine biomarkers in a clinical setting may pose additional obstacles but as our samples were analyzed in a research context, we do not have experience in this aspect. However, the time taken for processing of urine LRG in a clinical care setting had been reported to be 2 hours and at a cost of 26 USD in the study by Salo et al [22]. This was made possible by the new generation 'Ultra-Fast ELISA' assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual feasibility and logistic of analyzing urine biomarkers in a clinical setting may pose additional obstacles but as our samples were analyzed in a research context, we do not have experience in this aspect. However, the time taken for processing of urine LRG in a clinical care setting had been reported to be 2 hours and at a cost of 26 USD in the study by Salo et al [22]. This was made possible by the new generation 'Ultra-Fast ELISA' assay.…”
Section: Discussionmentioning
confidence: 99%
“…This was replicated in the study by Kharbanda et al [23], wherein despite achieving a 100% sensitivity and negative predictive value, the AUC was only 0.63 by ELISA. In another comparative study employing equal numbers of AA and non-AA cases, Salo et al showed improved performance when urine LRG was used in conjunction with the Pediatric Appendicitis score [22]. The combination demonstrated superior sensitivity of 95%, specificity of 90% and AUC of 0.94.…”
Section: Discussionmentioning
confidence: 99%
“…The precise function of LRG1 remains unknown, but accumulating evidences showed that LRG1 is closely correlated with various types of cancers, such as lung, oral, ovarian, gastrict, pancreatic and biliary tract cancers [14][15][16][17][18]. Moreover, LRG1 is identified as an inflammatory protein in human serum and highly expressed in various kinds of benign inflammatory and autoimmune diseases, including suspected acute appendicitis of children [19], activated ulcerative colitis [12], rheumatoid arthritis [20,21], adultonset Still's disease [22] and asthma [23]. Especially, Ahn et al found serum LRG, namely LRG1, is elevated in patients with SLE and correlates with disease activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical appearance in the younger children is often atypical, and misdiagnosis in 3 this age group is not rare, which can lead to an increased rate of perforation [2] . Clinical presentation, Pediatric Appendicitis Score (PAS), ALVARADO score, Computed tomography, ultrasound and blood tests, may be helpful in diagnose of AA, but it is difficult to confirm the type of appendicitis (simple or complicated appendicitis) [3][4][5] . Been able to diagnose uncomplicated vs. complicated appendicitis allows the surgeon to choose the best surgical approach ranging from antibiotics and delayed appendectomy to laparotomy [6] .…”
Section: Introductionmentioning
confidence: 99%